Powering Innovation: How High-Performance Computing Platform Revolutionizes University Research. - Wang, Dan; Quang Huynh, Anh Ngoc; Tang, Handong (Evaluation Review, 2026)
High-performance computing platforms (HPCP) serve as a critical component of institutional research infrastructure at universities, enhancing innovation efficiency. However, there is an absence of empirical research quantifying their impacts. Acknowledging this void, a difference-in-differences (DID) approach is employed in this study to systematically evaluate the influence of HPCP on university innovation efficiency. The findings reveal that: (1) universities with access to HPCP experience a significant improvement in innovation efficiency, with heterogeneities observed across regions, institutional rankings and university types; (2) HPCP drives innovation efficiency by attracting and cultivating top-tier researchers, expanding the scope of research activities and enabling the production of high-quality research outputs; and (3) the relationship between HPCP and innovation efficiency exhibits non-linearity, influenced by the quality and volume of research outputs as well as the presence of elite researchers. The contributions of this study are threefold viz: (1) providing empirical evidence quantifying HPCP's role in university innovation efficiency; (2) elucidating the mechanisms through which HPCP enhances innovation; and (3) identifying the non-linear relationship between HPCP and innovation efficiency, offering nuanced insights for policymakers to engender targeted strategies.